2009
DOI: 10.1007/s00421-009-1259-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of total haemoglobin mass: can it detect erythropoietin-induced blood manipulations?

Abstract: The purpose of the study was to reveal erythropoietin (epo) doping. It was recently suggested that the assessment of total haemoglobin mass (tHb) by means of the carbon monoxide re-breathing technique should be implemented in anti-doping work. Since epo may increase the haemoglobin concentration [Hb] simply by reducing plasma volume we injected eight human subjects with epo for 15 weeks and directly tested the feasibility hereof. Epo treatment increased [Hb] in all subjects at all time points (range 3.8-18.8%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 18 publications
2
11
0
Order By: Relevance
“…We should mention, however, that a recent study demonstrated the failure of total Hb mass to be a reliable marker for rHuEpo use (Lundby and Robach 2009). A limitation to the present study is that moderately trained university students do not represent the target population.…”
Section: Resultsmentioning
confidence: 88%
“…We should mention, however, that a recent study demonstrated the failure of total Hb mass to be a reliable marker for rHuEpo use (Lundby and Robach 2009). A limitation to the present study is that moderately trained university students do not represent the target population.…”
Section: Resultsmentioning
confidence: 88%
“…In this study, we performed two CO rebreathing tests on the same day in order to limit day-to-day variations. Indeed, interventions leading to only small changes in Hb mass and BVs are often applied in scientific studies (Prommer et al, 2008;Schumacher et al, 2008;Lundby & Robach, 2010;Mørkeberg et al, 2011;Hughson et al, 2012;Robach et al, 2012Robach et al, , 2014Siebenmann et al, 2012;Austin et al, 2014;Linnarsson et al, 2015;Wehrlin et al, 2016). The % TE when using the Rad-57 was, however, around 6%.…”
Section: Discussionmentioning
confidence: 99%
“…The CO rebreathing technique for detecting nonphysiologic increases in Hb mass is still investigational, 24,25 and besides practical difficulties related to this method, its potential inclusion in the blood passport may be problematic, 26 because the margin of variation when assessing Hb mass (biologic and measurement errors) would still allow athletes to manipulate with blood volumes that would increase exercise performance considerably. 27 Finally, it should also be considered that, from an athlete's viewpoint, it may not be desirable to breathe CO shortly before a competition as this may limit exercise performance.…”
Section: Rbc Transfusionmentioning
confidence: 99%